EVALUATION OF SCIENTIFIC ACTIVITIES OF THE UNIVERSITY RANKING METHOD - G. I. Dmitriev; E. A. Zakonnikov; V. A. Meyev; Y. V. Voronov (Дискурс, 2016)
The approach to assessment of effectiveness of scientific activity of higher educational institutions on the basis of a ranging technique is presented. This approach leans on indicators of scientific activity of the higher educational institutions of the Ministry of Education and Science of the Russian Federation presented in the departmental reporting. Comparison of indicators of personnel capacity of higher educational institutions with indicators of financing, effectiveness of research and development and training of research and educational personnel is the cornerstone of comparative assessment. Examples and results of ranging of higher educational institutions are given.